Clearinghouse for sport: Australia's knowledge sharing initiative - Kerr, C. (9. International Forum on Elite Sport, San Juan, Puerto Rico, August 24, 2015 - August 30, 2015, 2015)
The Clearinghouse for Sport (Clearinghouse), has been established to facilitate the exchange of information and knowledge across the sport sector and all levels of Australian governments. The Clearinghouse, will ultimately aim to facilitate the following types of knowledge: •"Know-how" (practical knowledge - information and examples of best practice); •"Know-what" (factual knowledge - statistics, results, sports facts and dates); •"Know-why" (scientific knowledge - research reports and scientific literature); and, •"Know-who" (network knowledge - expert directories and key contacts). The Clearinghouse represents a significant knowledge sharing programme of work by a number of leading Australian Sport Sector partners. The Australasian Sport Information Network (AUSPIN) is comprised of sports information and research professionals working across the sport and active recreation sector in Australia including Sport New Zealand and Oceania Sports Information Centre. AUSPIN members co-operate with each other by sharing expertise, information and experiences, as well as promoting, developing, and facilitating access to a broad range of sport information and research resources. • The Clearinghouse is open to all who wish to register as members. (Membership is free!) • Access to some Clearinghouse services and resources may be limited to certain member groups due to licensing arrangements with commercial publishers. • Access to content may also be restricted in instances where content owners are required to comply with copyright, privacy, and/or commercial in-confidence obligations. Clearinghouse members have access to a range of online services and licensed resources, including: • Portfolios of information covering key topics relevant to the sport sector • Full text electronic journals and research databases • Digital image files, and video and audio recordings • Current awareness and alerting services • Digitally archived Australian sports publications and reports • Research and references services • Discussion and collaboration networks